2019
DOI: 10.3892/etm.2019.8186
|View full text |Cite
|
Sign up to set email alerts
|

miR‑532‑5p promotes breast cancer proliferation and migration by targeting RERG

Abstract: Aberrant expression of microRNAs (miRNAs/miRs) mediates the initiation and progression of breast cancer. Therefore, it is important to investigate the molecular mechanisms of miRNAs and their effects on breast cancer progression. In the present study, miR-532-5p was highly expressed in breast cancer tissues compared with normal tissues. In addition, expression of ras-related and estrogen-regulated growth inhibitor (RERG), a tumor suppressor in breast cancer, was negatively correlated with miR-532-5p expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 35 publications
4
24
0
Order By: Relevance
“…39,40 Huang et al con rmed the abnormal expression of miR-532-5p in BC, and played a role as an oncogene. 41 Our experimental results con rmed that after overexpression of miR-532-5p, the level of CXCL2 mRNA decreased, and after inhibition of miR-532-5p expression, the level of CXCL2 mRNA increased, with signi cant statistical signi cance (Fig. 6B,C).…”
Section: Cxcl2 Expression Is Regulated By Mir-532-5psupporting
confidence: 69%
“…39,40 Huang et al con rmed the abnormal expression of miR-532-5p in BC, and played a role as an oncogene. 41 Our experimental results con rmed that after overexpression of miR-532-5p, the level of CXCL2 mRNA decreased, and after inhibition of miR-532-5p expression, the level of CXCL2 mRNA increased, with signi cant statistical signi cance (Fig. 6B,C).…”
Section: Cxcl2 Expression Is Regulated By Mir-532-5psupporting
confidence: 69%
“…An increasing number of studies have reported the important role of miRNAs in the treatment of various human cancers (23)(24)(25). The present study aimed to investigate the expressional patterns of miR-767 in NSCLC clinical samples and cells and to analyze the functional role of miR-767 in tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports indicate that miR-532 family members are dysregulated in various tumors and are associated with carcinogenesis, thus having been considered as potential novel therapeutic interventions for the treatment of specific tumors [44][45][46]. Furthermore, Chen et al found that serum EV miR-532-5p was significantly higher in control subjects versus F3/F4 fibrosis patients, using U6 as a reference gene [24].…”
Section: Discussionmentioning
confidence: 99%